DISTRIBUSI PENGGUNAAN BERAGAM JENIS VAKSIN COVID-19 DI WILAYAH KERJA PUSKESMAS GENTUNGAN, DESA GENTUNGAN, KECAMATAN BAJENG BARAT, KABUPATEN GOWA TAHUN 2022 - Basir, Hernawati; Istiana Purnamasari; Yuyun Sri Wahyuni; Delvi SJP; A Tenriugi Daeng Pine (Akademi Farmasi Yamasi Makassar, 2025)
In December 2019, Wuhan City in Hubei Province, China, became the epicenter of a novel coronavirus outbreak, later identified as SARS-CoV-2, the causative agent of COVID-19. Common symptoms of COVID-19 infection include fever, cough, and shortness of breath. This study aimed to determine the percentage distribution of various COVID-19 vaccine types administered at the Gentungan Public Health Center. Employing a non-experimental, descriptive approach, this research analyzed existing data without intervention on test subjects, utilizing a retrospective data collection method. The study population comprised 9,000 individuals, from which a sample of 383 participants was selected. The results indicated the following distribution of vaccine usage: Sinovac was administered to 236 individuals (61.61%), Pfizer to 61 individuals (15.92%), Moderna to 53 individuals (13.83%), and AstraZeneca to 33 individuals (8.61%). Sinovac was the most frequently administered vaccine, likely due to its ample availability and the lack of choice afforded to the public regarding vaccine selection.